The innovative ecosystem of university spin-offs: spaces, agents and transfer networks in the regional case studies of Madrid and Andalusia - Mecha-López, Rosa; Velasco-Gail, David (Revista de Estudios Andaluces, 2023)
In the context of the regional competitiveness of the Spanish Autonomous Communities (CC.AA.) based on the companies that transfer university knowledge, the Technology Transfer Offices (TTO) and the Scientific Parks from Universities, as well as the business incubators. This research analyzes in depth, through a participant observation methodology and qualitative techniques, the case of the innovative and entrepreneurial ecosystem of public universities in the Community of Madrid, and compares it with Andalusia. In the case of Madrid (uniprovincial region), together with the TTO, the role played by the Madri+d Foundation for Knowledge and its Technology-Based Entrepreneur Support Office as coordinator of a regional university network stands out, while in Andalusia the role of the regional TTO Network and the 10 science or technology parks that exist in the multi-provincial macro-region. The SWOT comparative diagnosis is complemented, as a conclusion, with a CAME strategy proposal for sustainable support for innovative ecosystems of university spin-offs.